2015
DOI: 10.1186/s13005-015-0086-5
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor enhances osteogenic differentiation of dental pulp stem cells in vitro

Abstract: IntroductionEpidermal growth factor (EGF) and basic fibroblast growth factor (bFGF) play an important role in extracellular matrix mineralization, a complex process required for proper bone regeneration, one of the biggest challenges in dentistry. The purpose of this study was to evaluate the osteogenic potential of EGF and bFGF on dental pulp stem cells (DPSCs).Material and methodsHuman DPSCs were isolated using CD105 magnetic microbeads and characterized by flow cytometry. To induce osteoblast differentiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 55 publications
(51 reference statements)
3
41
0
1
Order By: Relevance
“…Conversely, it was reported that in lower doses of EGF (5 µg/mL) and bFGF (10 µg/mL), neural differentiation increased and differentiation into mesoderm lineage decreased (10). Also, EGF increased osteogenic differentiation and morphological change of dental pulp stem cells (36).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, it was reported that in lower doses of EGF (5 µg/mL) and bFGF (10 µg/mL), neural differentiation increased and differentiation into mesoderm lineage decreased (10). Also, EGF increased osteogenic differentiation and morphological change of dental pulp stem cells (36).…”
Section: Discussionmentioning
confidence: 99%
“…Especially, as factors resulting in stimulating loss of AP activity in the pSSCs, bFGF, and EGF included in pSSCCM can be considered, supported by the previous reports that bFGF and/or EGF induce differentiation of stem cells in the extracellular signal-free niche (Carpenter and Cohen, 1990; Schuldiner et al, 2000; Del Angel-Mosqueda et al, 2015). Accordingly, physico-chemical and physiological niche derived from GDNF-mESCCM will be able to be used as a basic microenvironment for investigating effects of extracellular signals on undifferentiation or differentiation of pSSCs.…”
Section: Discussionmentioning
confidence: 52%
“…Interestingly, our previous study also demonstrated that GP‐12 can significantly promote the proliferation of osteoblasts by interaction with epidermal growth factor receptor (EGFR) (Fig. S3), the signaling of which can affect bone formation by regulating endochondral ossification, and plays an essential role in the remodeling of the extracellular matrix . β ‐Catenin is involved in both the Wnt/ β ‐catenin and the EGFR pathways.…”
Section: Resultsmentioning
confidence: 99%